Targeting the conserved coronavirus octamer motif GGAAGAGC is a strategy for the development of coronavirus vaccine - Lin, Ching-Hung; Hsieh, Feng-Cheng; Chang, Yu-Chia; Yang, Cheng-Yao; Hsu, Hsuan-Wei; Yang, Chun-Chun; Tam, Hon-Man-Herman; Wu, Hung-Yi (Virology journal, 2023)
Coronaviruses are pathogens of humans and animals that cause widespread and costly diseases. The development of effective strategies to combat the threat of coronaviruses is therefore a top priority. The conserved coronavirus octamer motif 5'GGAAGAGC3' exists in the 3' untranslated region of all identified coronaviruses. In the current study, we aimed to examine whether targeting the coronavirus octamer motif GGAAGAGC is a promising approach to develop coronavirus vaccine. Plaque assays were used to determine the titers of mouse hepatitis virus (MHV)-A59 octamer mutant (MHVoctm) and wild-type (wt) MHV-A59 (MHVwt). Western blotting was used for the determination of translation efficiency of MHVoctm and MHVwt. Plaque assays and RT-qPCR were employed to examine whether MHVoctm was more sensitive to interferon treatment than MHVwt. Weight loss, clinical signs, survival rate, viral RNA detection and histopathological examination were used to evaluate whether MHVoctm was a vaccine candidate against MHVwt infection in BALB/c mice. In this study, we showed that (i) the MHVoctm with mutation of coronavirus octamer was able to grow to high titers but attenuated in mice, (ii) with the reduced multiplicity of infection (MOI), the difference in gene expression between MHVoctm and MHVwt became more evident in cultured cells, (iii) MHVoctm was more sensitive to interferon treatment than MHVwt and (iv) mice inoculated with MHVoctm were protected from MHVwt infection. Based on the results obtained from cultured cells, it was suggested that the synergistic effects of octamer mutation, multiplicity of infection and immune response may be a mechanism explaining the distinct phenotypes of octamer-mutated coronavirus in cell culture and mice. In addition, targeting the conserved coronavirus octamer motif is a strategy for development of coronavirus vaccine. Since the conserved octamer exists in all coronaviruses, this strategy of targeting the conserved octamer motif can also be applied to other human and animal coronaviruses for the development of coronavirus vaccines, especially the emergence of novel coronaviruses such as SARS-CoV-2, saving time and cost for vaccine development and disease control.